ASSESSING THE PERCEPTION OF EDUCATORS ON DIGITAL TRANSFORMATION IN NIGERIAN HIGHER EDUCATION - Umar, Faruk Abdulhamid; Muhammad, Aminu Ahmad; Muhammad, Ardo Bamanga; Mohammed, Ibrahim (FUDMA Journal of Sciences, 2025)
Digital technology in the modern education system has expanded resources, eliminated barriers, improved the pedagogical context, and equipped students with 21st-century digital abilities during the learning process. Numerous studies examined how teachers perceived utilizing digital tools and the benefits and challenges of incorporating them into teaching. However, there is still no in-depth investigation of how educators view HEIs’ digital transition. This study empirically examines educators’ perceptions of the use of digital technology in teaching and learning activities via a quantitative research approach. The study collected data from educators at Nigerian HEIs using a survey questionnaire. The data was analyzed using descriptive and multivariate analyses. The results of the demographic analysis show that there are more male teachers (67%) than female teachers (33%), and 85% of them are between the ages of 18 and 50. Additionally, 44% of the teachers have been in the teaching profession for more than ten years. The results of descriptive analysis show that educators in HEIs support the use of digital technology in research, teaching, and learning. The results of regression analysis show that the main determinants of educators’ support for the digital transformation of Nigerian HEIs are educational value, institutional culture, and ease of use. The three factors are statistically significant and explain 45% of the variance.